1992
DOI: 10.1093/infdis/166.2.331
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interferon-  in Experimental Gram-Negative Sepsis

Abstract: To study the role of interferon-gamma (IFN-gamma) in gram-negative shock, mortality was compared in mice receiving either a monoclonal antibody to IFN-gamma (H22) or an irrelevant monoclonal antibody (L2-3D9) before or after an LD90 dose of Escherichia coli O111:B4. H22 given either 1 h before or 0.5 h after bacterial challenge protected mice from death (mortality at 48 h, 28% vs. 83%, P less than .001). Serum tumor necrosis factor-alpha (TNF alpha) levels and bacterial counts in blood and organs (liver, splee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1
2

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 17 publications
2
41
1
2
Order By: Relevance
“…As periodical comprehensive serology and histopathology revealed no indication of pathogens, the bacteria may have been enteric. This is consistent with the data indicating that IFN-y plays a significant role in the pathogenesis of Gram-negative sepsis (23).…”
Section: Discussionsupporting
confidence: 93%
“…As periodical comprehensive serology and histopathology revealed no indication of pathogens, the bacteria may have been enteric. This is consistent with the data indicating that IFN-y plays a significant role in the pathogenesis of Gram-negative sepsis (23).…”
Section: Discussionsupporting
confidence: 93%
“…These results suggest a protective role for IFN-ã in host responses to these pathogens. In contrast, it was reported that administration of a monoclonal antibody to IFN-ã before or after Escherichia coli challenge in an experimental gramnegative sepsis model protected mice from death [15]. In the present study, BALF IFN-ã levels in strain DT-X-infected mice were higher than those in strain DT-Sinfected mice at all time points.…”
Section: Discussioncontrasting
confidence: 85%
“…We show in this study that defective type I IFN signaling results in impaired host resistance to different extracellular pathogens, including GBS, S. pneumoniae, and E. coli. The effect of IFN-␣␤R deficiency was marked, with mortality surpassing that seen in the absence of IFN-␥ signaling, a function considered crucial for host defenses against intracellular (3), as well as extracellular (41,42,44) bacteria. Interestingly, IFN-␣␤R Ϫ/Ϫ and IFN-␥R Ϫ/Ϫ double KO mice showed an extremely severe, additive phenotype and quickly succumbed to challenge with few CFU of GBS.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-␥R Ϫ/Ϫ and double KO IFN-␣␤ and IFN-␥R Ϫ/Ϫ mice were also studied for comparison, because IFN-␥ is known to play a central role in defenses against intracellular (3,40) as well as extracellular (41,42) bacteria, including GBS (43)(44)(45). Fig.…”
Section: Ifn-␣␤r-deficient Neonatal Mice Are Hypersusceptible To Gbs mentioning
confidence: 99%